Who reaps the benefits in coaching research? : The case for an applied sociological approach - Kidman, L. (1998)
The views expressed in this paper are based on the author's experience of conducting research into coaching, and specifically the role of parents in the coaching of children's sport. In addition to data specific to the research topic, the results of the work also raise a number of questions about the beneficiaries of academic research in the area of coaching. Topics included are: - Value formation in children's sport - Parent's expectations - Performance evaluation and its effect on children